2018
DOI: 10.1109/jphot.2018.2871193
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Saturation Intensity Topological Insulator Saturable Absorber for Gigahertz Mode-Locked Solid-State Lasers

Abstract: The successful demonstration of Q-switched and mode-locked fiber-laser operations using a topological insulator (TI) as saturable absorber (SA) has opened an application window besides TI's originally expected features. However, to date, all-solid-state mode-locked lasers base on TISAs are still unavailable and became a desired goal not only due to their application as light sources, but also because of providing a way for deeper investigation of the nature of ultrafast dynamics present in TISAs. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In 2018, Wang et al demonstrated an all-solid-state mode-locked laser based on a large-area Bi Te SA mirror prepared by the spinning coating-co-reduction approach (SCCA), which had a repetition rate up to 1 GHz, output power up to 180 mW, and SNR of 61 dB [ 230 ]. These results indicates that TIs could be potential SAs in solid-state lasers for the generation of highly stable ultrafast pulses.…”
Section: Applications Of 2d Materials In Ultrafast Lasersmentioning
confidence: 99%
“…In 2018, Wang et al demonstrated an all-solid-state mode-locked laser based on a large-area Bi Te SA mirror prepared by the spinning coating-co-reduction approach (SCCA), which had a repetition rate up to 1 GHz, output power up to 180 mW, and SNR of 61 dB [ 230 ]. These results indicates that TIs could be potential SAs in solid-state lasers for the generation of highly stable ultrafast pulses.…”
Section: Applications Of 2d Materials In Ultrafast Lasersmentioning
confidence: 99%
“…However, special care can be taken in the cavity design to maintain sufficient modulation depth. For example, increasing the mode area at the SA become crucial to initiate QS-ML and even CW-ML under a relative low absorbed pump power of 100mW and 500 mW, respectively at a relatively high repetition rate of agigahertz [35].…”
Section: N * Population Inversion Density Of Laser Gain Media Fmentioning
confidence: 99%
“…It was expected that Ta 2 AlC-deposited tapered fiber would have the lowest mode-locking threshold, as it had the lowest saturation intensity compared to the 1.63% of the Ta 2 AlC-deposited SPF and 1.03% of the Ta 2 AlC-deposited arc-shaped fiber. A low saturation intensity would allow the SA to be saturated at a lower pump power to induce the mode-locking operation 79 .…”
Section: Fabrication and Characterization Of The Ta 2 Alc-deposited Tapered Arc-shaped And Side Polished Fibersmentioning
confidence: 99%